A New Disubstituted Polyacetylene Bearing 6‐Benzylaminopurine Moieties: Postfunctional Synthetic Strategy and Sensitive Chemosensor Towards Copper and Cobalt Ions. Issue 9 (15th January 2013) - Ou, Daxin; Zhang, Liang; Huang, Yanfen; Lou, Xiaoding; Qin, Jingui; Li, Zhen; Tang, B. Z.; Liu, B.
Abstract A new 6‐benzylaminopurine‐functionalized disubstituted polyacetylene (P2) with strong green fluorescence is successfully synthesized by utilizing the postfunctional method. The polymer is soluble in common organic solvents, and its strong green fluorescence can be quenched by copper and cobalt ions with a detection limit down to 1.0 × 10−8 (0.64 ppb) and 3.3 × 10−8 mol L−1 (1.94 ppb), respectively. Moreover, not much interference is observed from other metal ions, including Li+, Na+, K+, Fe3+, Fe2+, Ni2+, Hg2+, Mg2+, Al3+, Zn2+, Mn2+, Pb2+, Ba2+, Ca2+, Cd2+, Ag+, and Cr3+. Furthermore, P2 can be put into application using test strips, making P2 a practical, sensitive, and selective copper and cobalt probe.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>